Gallium ions incorporated silk fibroin hydrogel with antibacterial efficacy for promoting healing of Pseudomonas aeruginosa-infected wound - Zheng, Hui; Huang, Zhida; Chen, Tongxin; Sun, Yafeng; Chen, Shouqing; Bu, Guangming; Guan, Hongcai (Frontiers in Chemistry, 2022)
The continual resistance to antibiotics and the generation of a series of bacterial infections has emerged as a global concern, which requires appropriate measures and therapeutics to address such a menace. Herein, we report on Silk fibroin (SF) hydrogel with good biocompatibility and biodegradability fabricated through the crosslinking of the SF of different concentrations with Gallium nitrate (Ga (NO3)3) against Pseudomonas aeruginosa. However, the SF: Ga = 500: 1 (w/w) (SF/Ga) demonstrated a good bactericidal and wound healing effect as a result of the moderate and prolonged release of the Ga3+ following the gradual degradation of the hydrogel. The Ga3+, known for its innovative nature acted as a crosslinked agent and a therapeutic agent employing the “Trojan horse” strategy to effectively deal with the bacteria. Also, the Ga3+, which is positively charged neutralizes the negative potential value of the SF particles to reduce the charge and further induce the β-sheet formation in the protein structure, a characteristic of gelation in SF. The morphology showed a fabricated homogenous structure with greater storage modulus- G’ with low loss modulus- G'' modulus demonstrating the mechanical performance and the ability of the SF/Ga hydrogel to hold their shape, at the same time allowing for the gradual release of Ga3+. A demonstration of biocompatibility, biodegradability, bactericidal effect and wound healing in in vitro and in vivo present the SF/Ga hydrogel as an appropriate platform for therapeutic and for antibacterial wound dressing.